Pembelajaran Daring Matematika di Era Pandemi Menggunakan Kanal Youtube dengan Pendekatan Inkuiri - Feriyanto Feriyanto; Taswirul Afkar; Syifa’uliyah Syifa’uliyah (Institut Binamadani Indonesia, 2022)
This research aims to examine online learning in pandemic era using the Youtube channel with an inquiry approach. Student are axpected to be able to use Youtube for study to solve mathemathics learning problem online in the pandemic era in daily life. Online learning with an inquiry approach studied based pretest and post-test instruments. The reseach method used qualitative research with a descriptive research approach and implemented by online in this pandemic era. The sample included two students of ten grade in Samarinda and Mojokerto from odd semester year 2020/2021. This research instruments used essay questions to examine student’s problem-solving skills. The result of this research show that lack of student’s accuracy in solving problem, resulting in low post-test score obtained by student. Online learning in the pandemic used Youtube channel with inquiry approach has not been able effective to do.